The simulation analysis of stator flux droop minimization in direct torque control open-end winding induction machine - Muhammad Zaid Aihsan; Auzani Jidin; Siti Azura Ahmad Tarusan; Tole Sutikno (Institute of Advanced Engineering and Science, 2023)
Direct torque control (DTC) using dual-inverter technique is one of the best topologies for electric vehicle (EV) as it offers abundant selection of voltage vectors to drive the induction machine (IM). This dual-inverter technique also more reassuring as the system still workable even any of its voltage supply is disrupted or the power pack is drained. However, during the uneven voltage supply, the movement of voltage vectors is interrupted and will move obliquely especially in medium voltage vectors. This situation will lead to the faulty movement of the voltage vectors in the default sector definitions and lead to huge flux droop, which later could impose to distort phase current. This paper proposes an optimal sector definition based on the preset voltage ratio between the two inverters. The voltage vectors can be mapped tangentially to the flux vector, minimizing the flux droop and improving the phase current waveform when the proposed sector is utilized. The effectiveness of the proposed sector is tested using MATLAB/Simulink software and the exact parameter from the induction machine.